A SIMPLE SYNTHESIS OF NICKEL OXIDE NANOTUBE USING HIGH VOLTAGE ELECTROLYSIS - Pramana, Yanatra Budi; Setiawan, Bramianto; Prihono, Prihono; Utomo, Yitno; Subandowo, Marianus; Budipramana, Krisyanti (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Recently, the development of nanoparticle nickel oxide has increased due to their potential application such as biosensors, catalysts, solar cells, supercapacitors, and batteries. In this work, the addition of CTAB for nickel oxide nanoparticle synthesis using electrolysis was investigated. Â The nickel plates were used as anode and cathode in the electrolysis process. The process was operated at a constant voltage of 60 V for 30 minutes. The XRD result showed conformity with the Nickel oxide diffraction pattern. Meanwhile, the impurity from nickel hydroxide peaks still appeared. From FTIR characterization also indicates the band of Ni-O stretching vibration. The morphology characterization of nickel oxide using Scanning Electron Microscopy (SEM) showed the nanotube structure, while Transmission Electron Microscopy showed the nanoparticle size from 250.44 to 325.60 nm in length. On the other hand, the transformation of Ni(OH)2 to NiO has been shown using TGA characterization.